The Effect of High Temperature on Styrene Monomer Migration from Polystyrene Cup - Muhammad Shafiq bin Mat Shayuti, Muhammad Shafiq (2008)
In general as temperature increased, the migration of styrene from the PS cup into the cooking oil also increased. As the temperature increased, the molecules move faster due to higher kinetic energy and therefore collide more frequently. Thus, the proportion of collisions that could overcome the activation energy for the reaction increased with temperature, resulting in higher migration rate.